Pengaruh Minat Membaca dan Kebiasaan Belajar terhadap Prestasi Bahasa Indonesia Siswa Kelas Atas SD Negeri 1 Munggung Karangdowo Klaten Tahun 2015/2016 - Retnaningsih, Endah (2016)
This study aims to determine: (1) the effect of interest to read the achievements of Indonesian students upscale SD Negeri 1 Munggung Karangdowo Klaten, (2) the impact of study habits on the achievement of Indonesian students upscale SD Negeri 1 Munggung Karangdowo Klaten, and (3) the effect of interest in reading and learning habits of the Indonesian student achievement upscale SD Negeri 1 Munggung Karangdowo Klaten. This research is a quantitative research. The population in this study were students upscale (4, 5, 6) SD Negeri 1 Munggung Karangdowo Klaten. The data collection technique using a questionnaire (questionnaire) and documentation. Instruments tested the validity and reliability test. While the analysis is the prerequisite test for normality and linearity test. Data analysis techniques used multiple regression analysis and correlation of product moment. The results showed: 1) there are significant interest in reading the Indonesian student achievement upscale Munggung Karangdowo SD Negeri 1 Klaten, with values obtained t_hitung > t_tabel amounted to 4.997 > 2.008 and sig. 0.000 < 0.05, 2) there is the influence study habits to Indonesian students' achievement upscale Munggung Karangdowo SD Negeri 1 Klaten, with values obtained t_hitung > t_tabel amounted to 2.143 > 2.008 and sig. 0.037 < 0.05, 3) there are significant interest in reading and learning habits of the Indonesian student achievement upscale Munggung Karangdowo SD Negeri 1 Klaten, with a value F_hitung > F_tabel amounted to 14.747 > 3.17 and sig. 0.000 < 0.05.